2016
DOI: 10.1159/000447936
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognosis of Cardiorenal Syndrome Type 1 in Elderly Chinese Patients: A Retrospective Observational Cohort Study

Abstract: Background/Aims: Cardiorenal syndrome type 1 (CRS1) is a syndrome characterized by a rapid worsening of cardiac function leading to acute kidney injury (AKI). The aims of this study were to investigate the risk factors and the prognosis of CRS1 in elderly patients. Methods: A total of 312 elderly patients (≥60 years old) with acute heart failure (AHF) were studied. They were assigned as CRS1 (suffered from in-hospital AKI) or NCRS1 (without AKI) group. Clinical and laboratory data were recorded. Univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Recent evidence in other clinical scenarios comes from isolated studies involving a total of more than 2500 patients. Hypoalbuminemia has been associated with AKI-related morbidity/mortality in patients with severe rhabdomyolysis[38], pyogenic liver abscess[65], contrast-induced nephropathy[66], hospital-acquired AKI[67,68], and in critically ill patients requiring continuous RRT[69], geriatric patients[70-72], and those undergoing open ventral hernia repair[73]. …”
Section: Other Indicationsmentioning
confidence: 99%
“…Recent evidence in other clinical scenarios comes from isolated studies involving a total of more than 2500 patients. Hypoalbuminemia has been associated with AKI-related morbidity/mortality in patients with severe rhabdomyolysis[38], pyogenic liver abscess[65], contrast-induced nephropathy[66], hospital-acquired AKI[67,68], and in critically ill patients requiring continuous RRT[69], geriatric patients[70-72], and those undergoing open ventral hernia repair[73]. …”
Section: Other Indicationsmentioning
confidence: 99%
“…Even a slight increase in creatinine will increase the possibility of a poor prognosis, by increasing the risk of mortality, progression to CKD or ESRD, or a cardiovascular event [9, 10]. However, AKI is preventable and can even be reversed in early stages [1].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study suggested that the use of BB was protective for in-hospital mortality in patients with ADHF who were complicated by WRF. 37 Further studies can be warranted to assess the association between BB and mortality in patients with ADHF and WRF.…”
Section: Clinical Researchmentioning
confidence: 99%